AWARENESS OF MEDICINAL APPLICATIONS OF ALTERNANTHERA SESSILIS AMONG DENTAL STUDENTS - Masilamani, Nithyanandham; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Alternanthera sessilis is a yearly or perpetual prostate weed, found all through the more smoking piece of India, climbing to a height of 1200 m. The plant has been scientifically demonstrated to comprise substance constituents like α- and β-spinasterols, lupeal disconnected from roots. The aim of the study was to assess the awareness of medicinal applications of Alternanthera sessilis among dental students.A cross-sectional study was done with a self-administered questionnaire with 10 questions circulated among 100 dental students. The questionnaire assessed the awareness about Alternanthera sessilis therapy in medical applications, their wound healing properties, antiglycaemic applications, memory enhancement applications, anti-ulcer, diabetic, and anti-inflammatory activity. The responses were recorded and analysed. 91% of the respondents were not aware of the medicinal applications of Alternanthera sessilis therapy. 85% were not aware of the wound healing properties of Alternanthera sessilis therapy. 87% were not aware of the antiglycemic properties of Alternanthera sessilis therapy. 85% were not aware of the memory enhancement properties of Alternanthera sessilis therapy. 89% were not aware of the anti-ulcer properties of Alternanthera sessilis therapy. 83% were not aware of the antidiabetic effects of Alternanthera sessilis therapy. 89% were not aware of the anti-inflammatory properties of Alternanthera sessilis therapy. The awareness about the use of Alternanthera sessilis therapy in medical applications is low among dental students.Increased awareness programs and sensitization and continuing dental education programs, along with greater importance to the curricular modifications, can further enhance knowledge and awareness about Alternanthera sessilis therapy.